Maternal Health Interventions and Other Determinants of Childhood Stunting: A Cross-Sectional Study - Astuti Setiyani; Suparji Suparji; Hery Sumasto; Alfi Rusdianti (Borneo Scientific Publishing, 2026)
Stunting remains a major public health problem in developing countries and is associated with impaired cognitive development, poor educational attainment, reduced productivity, and an increased risk of chronic diseases later in life. Maternal health during pregnancy is considered a key determinant of child growth and development. This study aimed to identify factors associated with stunting among children under five years of age, with a particular focus on maternal health interventions during pregnancy, including antenatal care, nutritional monitoring, and micronutrient supplementation. A cross-sectional study was conducted among 140 mothers of children under five years of age attending four community health centers in Surabaya, East Java, Indonesia. Participants were selected using proportionate stratified random sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics, Chi-square tests, and binary logistic regression, with a significance level of p < 0.05. The results of the study show that the prevalence of stunting was 21.4%. Bivariate analysis showed that maternal health interventions were significantly associated with stunting (p = 0.040), while breastfeeding and complementary feeding practices demonstrated a marginal association (p = 0.074). Child nutritional intake (p = 0.271), immunization and growth monitoring (p = 1.000), and environmental sanitation (p = 0.526) were not significantly associated with stunting. Multivariable logistic regression analysis identified maternal health intervention as the most influential factor associated with stunting (OR = 0.46; 95% CI: 0.23–0.94; p = 0.032), indicating a protective effect against stunting among children under five years of age. In conclusion, maternal health interventions during pregnancy play a significant role in reducing the risk of childhood stunting. Strengthening antenatal care services, maternal nutrition support, and health education for pregnant women should therefore be prioritized as part of integrated stunting prevention strategies at the primary healthcare level.